Developing Oral Language Skills in Middle School English Learners. Issue 1 (2nd January 2018) - Fisher, Douglas; Frey, Nancy
ABSTRACT: Oral language development can help English learners develop academic proficiency with the English language. In this investigation, at one middle school, teachers focused on improving oral language skills. Using a formative experiment process, the teachers developed an intervention to accomplish their pedagogical goal and then tracked data to see if their program worked. They made changes in response to student data and adjusted the intervention until the results were more positive.